Evaluation of upper blepharoplasty outcome ‒ objective measurements and patient satisfaction - Nikolić, Jelena; Marinković, Marija; Jovanović, Mladen; Mijatov, Ivana; Božić, Teodora (Vojnosanitetski pregled, 2022)
Background/Aim. Upper blepharoplasty is one of the most often performed aesthetic operations and is indicated for periorbital rejuvenation or correction of some functional problems. The aim of the study was to evaluate the outcome of this procedure and to assess patients’ satisfaction and possibilities of objective measurement of operative results. Methods. A two-year prospective observational study was conducted among female patients who had upper blepharoplasty done by the same surgeon. Data were collected from medical documentation, questionnaire, and objective measurements conducted via standardized digital photographs taken before and two months after surgery. Tarsal platform show (TPS) and brow fat span (BFS) were measured at three points (P1, P2, P3) before and two months after the surgery. A questionnaire conducted before surgery and two months after it included general complaints considering upper eyelids (visual field narrowing, fallen eyelids, the sensation of heavy eyelids, raising head backward in order to enhance vision, headache), patientsʼ assessment of eyelid asymmetry and an additional questionnaire after surgery included questions for the surgeon and patients concerning satisfaction with treatment outcome. Results. This study involved 50 female patients aged between 33 and 67 years (49.98 ± 8.6 years). There was a statistically significant difference in all points for TPS and BFS measurements before and after the operation. No significant asymmetries were noticed between eyes neither before nor after surgery. There was a statistically significant difference in operation success among 3 age categories in TPS-P1 (c2 = 13.089, df = 2, p = 0.001) and TPS-P2 (c2 = 8.386, df = 2, p = 0.015) with best results achieved in older patients (> 55 years). There was strong positive, statistically significant correlation between patient’s and surgeon’s satisfaction (r= 0.704, p = 0.002), as well as between patients’ satisfaction and their age (r = 0.704, p = 0.002). Conclusion. Realistic expectations, adequate information about the surgery and possible complications, are essential to satisfied patients. Objective measurements correlate with patientsʼ satisfaction and together with photographs can be a useful tool in communication with them.